PENGARUH TERAPI AKUPUNKTUR TERHADAP FUNGSI KARDIOVASKULER (SBP, DBP, MAP, RPP, PP) PADA KASUS HIPERTENSI DI GRIYA AKUPUNKTUR NY. INDY KEDIRI - Eka Deviany Widyawaty; Heni Nur Kusumawati; Made Indisari Rohbana (Jurnal Medicare, 2025)
Hypertension is one of the main risk factors for cardiovascular diseases and can increase both morbidity and mortality. The management of hypertension is not limited to pharmacotherapy but can also be addressed through non-pharmacological approaches such as acupuncture. This study aims to determine the effect of acupuncture therapy on cardiovascular function, measured through SBP, DBP, MAP, RPP, and PP parameters in hypertensive patients at Griya Akupunktur Ny. Indy Kediri. The research design used was a pre-experimental one-group pretest-posttest design with a sample of 30 participants selected through purposive sampling. The intervention was carried out over 14 days using specific acupuncture points. Data were collected before and after the therapy and analyzed using the paired sample t-test. The results showed a significant decrease in all cardiovascular function parameters after therapy, with p-values < 0.001 for SBP, HR, MAP, RPP, and PP, and p < 0.05 for DBP. Based on these findings, it can be concluded that acupuncture therapy is effective in lowering blood pressure and cardiac workload, as well as improving cardiovascular regulation. Acupuncture can serve as a promising complementary therapy in the holistic management of hypertension.